Modeling Irrigation Water Demand in a Tropical Paddy Cultivated Area in the Context of Climate Change - Nurul Nadrah Aqilah, Tukimat; Sobri, Harun; Shamsuddin, Shahid (ASCE, 2017)
Irrigation is the major user of total water use in most of the tropical countries located in Southeast Asia. Therefore, knowledge on future changes in irrigation demand in the context of climate change is very important for long-term planning and management of water resources of the region. This paper investigated the changes in irrigation water demand in an intensive irrigated area of Malaysia under climate change scenario. Global circulation models (GCMs) outputs are downscaled using statistical downscaling model (SDSM) to project the future changes in rainfall and temperature at local scale. The irrigation water demand estimation model known as CROPWAT is calibrated and validated with historical data and then used to project the future changes in irrigation demand under SDSM projected climatic condition. The results show that temperature and rainfall in the area will increase by 0.2° C and 4% per decade, respectively over the time period 2020–2099. The changes in climate will reduce irrigation water demand at a rate of 0.9% per decade in the area. However, the irrigation demand will be much more variable in future, and therefore, the major challenge in water resources management will be to handle the uncertainty. It is expected that the seasonal and annual variations in irrigation demand projected by the study will help in operating reservoirs and sustainable management of water resources in the region in the context of climate change.